2016
DOI: 10.1128/jvi.02675-15
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Inhibitor of cGAS (KicGAS), Encoded by ORF52, Is an Abundant Tegument Protein and Is Required for Production of Infectious Progeny Viruses

Abstract: Although Kaposi's sarcoma-associated herpesvirus (KSHV) ORF52 (also known as KSHV inhibitor of cGAS [KicGAS]) has been detected in purified virions, the roles of this protein during KSHV replication have not been characterized. Using specific monoclonal antibodies, we revealed that ORF52 displays true late gene expression kinetics and confirmed its cytoplasmic localization in both transfected and KSHV-infected cells. We demonstrated that ORF52 comigrates with other known virion proteins following sucrose gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…We selected three viral genes with different expression kinetics for the following reasons: (i) ORF6 was selected because of its well-documented function in the establishment of replication compartments (RCs) in infected cells that should lead us to identify KSHV DNA replicating cells (39,40); (ii) LANA was selected to visualize location and track copy number of latent KSHV episomes during cell proliferation (41); and (iii) ORF52 (tegument protein) was selected because of its higher expression during replication. Fusion of enhanced green fluorescent protein (EGFP) to the ORF52 N terminus also was shown to have little effect on the production of KSHV virions in culture media (42). Three fluorescence tags (mBFP2, mCherry, and mCardinal) were selected based on their relative brightness and separation of fluorescence emission peaks.…”
Section: Resultsmentioning
confidence: 99%
“…We selected three viral genes with different expression kinetics for the following reasons: (i) ORF6 was selected because of its well-documented function in the establishment of replication compartments (RCs) in infected cells that should lead us to identify KSHV DNA replicating cells (39,40); (ii) LANA was selected to visualize location and track copy number of latent KSHV episomes during cell proliferation (41); and (iii) ORF52 (tegument protein) was selected because of its higher expression during replication. Fusion of enhanced green fluorescent protein (EGFP) to the ORF52 N terminus also was shown to have little effect on the production of KSHV virions in culture media (42). Three fluorescence tags (mBFP2, mCherry, and mCardinal) were selected based on their relative brightness and separation of fluorescence emission peaks.…”
Section: Resultsmentioning
confidence: 99%
“…By mass spectrometry analysis of mature KSHV virions, several tegument proteins, such as open reading frame 33 (ORF33), ORF38, ORF45, ORF52, ORF55, ORF63, ORF64, and ORF75, have been identified (11). Among these tegument proteins, some are important for innate immune modulation to facilitate the establishment of persistent infection (12)(13)(14)(15)(16)(17), and some are involved in virion tegumentation, assembly, and trafficking (18)(19)(20)(21)(22)(23). However, how these tegument proteins are packaged into virions is still largely unknown.…”
mentioning
confidence: 99%
“…Nevertheless, we also found that ORF52 is able to induce alterations in the MT cytoskeleton not only in hTERT-RhF but also in 293T cells (not shown), suggesting that the effects are not cell type specific. Of note, a recent report that appeared as we prepared the present study showed that KSHV ORF52 also associates with MTs ( 56 ). Although, in our hands, the effect from the overexpression of the KSHV ortholog is significantly less pronounced than that with RRV ORF52, this congruence suggests a likely conservation of function among gammaherpesviruses.…”
Section: Discussionmentioning
confidence: 49%